Martensina thailandica gen. et sp. nov. a freshwater ostracod representing a new subfamily of Cyprididae, Martensininae subfam. nov. (Crustacea: Ostracoda) from Thailand - Savatenalinton, Sukonthip (European Journal of Taxonomy, 2022)
Martensina thailandica gen. et sp. nov., a freshwater ostracod species representing a new subfamily, Martensininae subfam. nov., in the family Cyprididae, is here described from a swamp in Maha Sarakham Province, Thailand. The new genus and species is mainly characterized by the 7-segmented antennula which has a Rome organ and remarkably long aesthetasc ya, the morphology of the sexually dimorphic antenna (A2), the markedly elongated A2 terminal segment, the short and thin α- and β-setae on the mandibular palp, the elongated terminal segment of the maxillula, the obviously 2-segmented male prehensile palp, the presence of d1 and d2 setae on the protopod of the second thoracopod (T2), the sexually dimorphic T2, the distinctive terminal segment of the third thoracopod bearing three long setae, the well-developed caudal ramus, the large hemipenis which has a complex internal structure, and the Zenker organ with funnel-shaped ends and numerous spiny whorls.